Welfare packages and staff performance at benue state independent electoralcommission, Makurdi, Nigeria / Oravee Aule and Ahmed Rashidi - Aule, Oravee; Rashidi, Ahmed (Universiti Teknologi MARA, 2021)
The study examined how welfare packages affected staff performance at Benue State Independent Electoral Commission, Makurdi. The specific objectives were to ascertain how medical care services, housing facilities and recreational facilities affected staff performancein the organization. Primary and secondary sources of information were used for study. The population of the study consisted of 259 staff of the organization. The data were collected and analyzed using descriptive statistical tools such as tables and simple percentages., and the stated hypotheses tested using Chi-square. Findings of the study indicated that medical care services, housing facilities, andrecreational facilities have significant effect on staff performance. The study therefore concluded that employee welfare packages have significant positive effect on staff performance. It was therefore recommended that the organization should ensure the improvement of medical care services, housing facilities and recreational facilities for employees to improve their living standards for maximum job performance.